2012
DOI: 10.1002/path.3963
|View full text |Cite
|
Sign up to set email alerts
|

Yield of routine molecular analyses in colorectal cancer patients ≤70 years to detect underlying Lynch syndrome

Abstract: Although early detection of Lynch syndrome (LS) is important, a considerable proportion of patients with LS remains unrecognized. We aimed to study the yield of LS detection by routine molecular analyses in colorectal cancer (CRC) patients until 70 years of age. We prospectively included consecutive CRC patients ≤70 years. Tumour specimens were analysed for microsatellite instability (MSI), immunohistochemical mismatch-repair protein expression and MLH1-promoter methylation. Tumours were classified as either: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 56 publications
2
52
0
1
Order By: Relevance
“…ing had been driven by the use of clinical guidelines based on age and family history, such as the Amsterdam (Vasen et al, 1991;Vasen et al, 1999) and Bethesda criteria (Rodriguez-Bigas et al, 1997;Umar et al, 2004). However, it has been shown that up to 50% of mutation carriers do not fulfill the Amsterdam criteria and 40-45% of families fulfilling Amsterdam criteria do not have MSI on tumor testing (Pino and Chung, 2011;Syngal et al, 2000) The Bethesda guidelines incorporate tumor histopathologic features and while more sensitive, can still miss 12-28% of LS cases (Canard et al, 2012;Hampel et al, 2008;Julie et al, 2008;Moreira et al, 2012b;van Lier et al, 2012). In 2009, the 'Jerusalem criteria' recommended IHC or MSI testing be carried out on all CRC, where the patient is under the age of 70 at diagnosis (Boland and Shike, 2010).…”
Section: Age and Clinical-based Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…ing had been driven by the use of clinical guidelines based on age and family history, such as the Amsterdam (Vasen et al, 1991;Vasen et al, 1999) and Bethesda criteria (Rodriguez-Bigas et al, 1997;Umar et al, 2004). However, it has been shown that up to 50% of mutation carriers do not fulfill the Amsterdam criteria and 40-45% of families fulfilling Amsterdam criteria do not have MSI on tumor testing (Pino and Chung, 2011;Syngal et al, 2000) The Bethesda guidelines incorporate tumor histopathologic features and while more sensitive, can still miss 12-28% of LS cases (Canard et al, 2012;Hampel et al, 2008;Julie et al, 2008;Moreira et al, 2012b;van Lier et al, 2012). In 2009, the 'Jerusalem criteria' recommended IHC or MSI testing be carried out on all CRC, where the patient is under the age of 70 at diagnosis (Boland and Shike, 2010).…”
Section: Age and Clinical-based Criteriamentioning
confidence: 99%
“…Lynch syndrome (formerly hereditary non-polyposis colorectal cancer [HNPCC]) is the most common heritable cancer predisposition syndrome and is characterised by an increased predisposition to certain cancers, most notably CRC (Vasen et al, 2007). Lynch syndrome tumours are caused by autosomal dominant mutations in the DNA MMR system (Bonadona et al, 2011;Jass, 2007;Kovacs et al, 2009;Lagerstedt Robinson et al, 2007;Ligtenberg et al, 2009;Lynch et al, 2009;van der Klift et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, 12 to 28% of Lynch syndrome patients may be missed if testing is guided by these criteria and universal testing, that is, testing of all CRC specimens has a greater sensitivity for the identification of Lynch syndrome patients compared with the Bethesda Guidelines, but also compared with other selective strategies (e.g. tumor testing of patients with CRC < 70 years of age or older patients meeting the Bethesda Guidelines) [92,93,94,95]. It is of note that even 70% of Lynch syndrome patients may be missed when the selection is based on the pathological Bethesda criteria only, that is, CRC in a patient aged less than 50 years, CRC with MSI-H phenotype in a patient aged less than 60 years, or meta-/synchronous CRC regardless of age [43].…”
Section: Microsatellite Instability Testing In the Routine Settingmentioning
confidence: 99%
“…Identifying patients who have LS after their first cancer diagnosis presents the opportunity for risk-reducing strategies such as increased surveillance or prophylactic surgery. Proponents have advocated a variety of alternate screening strategies, including mathematical algorithms to predict MMR gene mutation carriers based on personal and family history [22] and broader, even universal, tumor mutation testing [14,19,23,24]. However, the inconsistency between pathologists in evaluating the histopathological features of MSI tumors [25,26,27,28] highlights the limitations of these clinical strategies.…”
Section: Discussionmentioning
confidence: 99%